Are capacity deficits in local government leaving the Amazon vulnerable to environmental change?. (December 2017) - Malhado, Ana C.M.; Costa, Marcos H.; Correia, Ricardo A.; Malhado, Acácia C.M.; de la Fuente, Maria Fernanda C.; da Costa, Amesson M.; Batinga, Juliana Verçosa; Bragagnolo, Chiara; Ladle, Richard J.
Highlights: Large areas of the Brazilian Legal Amazon are at risk of climatically mediated environmental change. Implementation of environmental policy in Brazil has largely been devolved to municipal government. We show that municipal capacity to develop and implement environmental policy in the Amazon is low. There is no evidence that municipalities at most risk of catastrophic environmental change are proactively responding. Technical assistance should be focused on smaller, less developed municipalities. Abstract: The last 20 years have seen remarkable progress in monitoring and modelling environmental change in the Amazon region. As a result, scientists and policy makers now have robust and spatially explicit knowledge and forecasts of critical phenomena such as deforestation and bioclimatic uncertainty. However, whether this knowledge is used to support the implementation of policies and initiatives to cope with environmental changes in the Amazon depends on the ability of the political institutions to proactively integrate the scientific evidence into land planning at multiple spatial scales. In Brazil, municipalities are constitutionally responsible for legislating on land planning and therefore have a power to significantly influence the future trajectory of environmental change. Here, we assess the environmental capacity of municipalities in the Brazilian legal Amazon based on data from a self-assessment survey and from the Brazilian Institute of Geography and Statistics database. Municipalities generally have a low level of institutional capacity and there is no evidence that the municipalities most at threat from environmental change are taking proactive measures to reduce their vulnerability. We argue that structural reforms and capacity raising initiatives are urgently needed, especially in smaller, less economically developed municipalities located in areas at high risk of imminent environmental change.